Stenocereus species with brown areoles: a key and descripitions - Arreola-Nava, Hilda J.; Terrazas, Teresa (Instituto de Ecología, A.C., 2003)
A key and descriptions of Stenocereus species with brown areoles are presented based on the revision of herbarium specimens, field observations, and intensive field collections. The species of Stenocereus with brown areoles are seven and can be distinguished from other species of the genus up to day known in their glandular trichomes conferring a dark color to all their areoles and in their distribution centered in western Mexico.